A watermarking-based authentication and image restoration in multimedia sensor networks. (2018) - Hai, Huang; Qing, Xie Dong; Ke, Qi
In this paper, we propose a novel watermarking-based secure image acquisition scheme for multimedia sensor networks (MSNs), which provides support for image authentication and restoration. In the proposed scheme, the sensor node groups image frames. Two successive frames compose the non-overlapping authentication and restoration group. The watermarking bits, which are the version of the down sampling image, are computed from the first image and reversibly embedded into the second image. The sink does the verification and restoration by reversible watermark. Compared to previous work, our approach can not only implement authentication but also improve image quality. Experimental results show that our scheme can achieve gains in terms of authentication and packet loss tolerance to improve the image quality.